1982
DOI: 10.1177/002580248202200111
|View full text |Cite
|
Sign up to set email alerts
|

Thin Layer Chromatography as a Routine Appropriate Technique for the Determination of Bipyridylium Herbicides in Post Mortem Human Tissues

Abstract: A thin layer chromatographic procedure for the detection of bipyridylium compounds in post-mortem human tissues is described. To verify the suitability of the method, human biological samples originating from two fatal poisoning cases, are analyzed. In the first case, an amount of Gramoxone® (Paraquat) was taken orally. Death occurred after ± 30 hours without any specific treatment. The second case is concerned with an ingestion of Reglone® (Diquat), followed by death after 5 days of intensive care treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…11 Over the period 1968-1999, only 30 cases of diquat poisoning were reported in detail in the literature, of which 13 (43%) [19][20][21][22][23]25,29,30 were fatal.…”
Section: Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Over the period 1968-1999, only 30 cases of diquat poisoning were reported in detail in the literature, of which 13 (43%) [19][20][21][22][23]25,29,30 were fatal.…”
Section: Featuresmentioning
confidence: 99%
“…13,19,28,34 As a consequence, generalized abdominal pain, 15,25,[28][29][30]32 vomiting, 13,14,19,[24][25][26][28][29][30]35 and diarrhea 12,24-26,28-32 can occur within a few minutes of ingestion.…”
Section: Systemic Toxicitymentioning
confidence: 99%
“…These incidents have involved mostly suicidal and some accidental diquat ingestion cases. Signs and symptoms associated with skin and inhalation overexposure to diquat concentrate or spray mist are primarily displayed by manifestation of tissue irritation (Schonborn, 1971;Crabtree, 1977;Vanholder, 1981;Van Den Heede, 1982;Hantson, 2000;Schmidt, 2000).…”
Section: Human Case Reports and Studiesmentioning
confidence: 99%
“…Based on the weight of the evidence from the diquat toxicology investigations, occupational use and clinical findings, the chemical is not considered to be a neurotoxin. No neurological effects have been reported from incidental ingesting of spray dilution or swallowing of diquat treated water while swimming or in situations where the treated water was used as a drinking water source (Swan, 1969;Schonborn, 1971;Crabtree, 1977;Vanholder, 1981;Van Den Heede, 1982;Wojeck, 1983;Hantson, 2000;Schmidt, 2000).…”
Section: Human Neurological Case Reportsmentioning
confidence: 99%
“…To the knowledge of the authors, a wide variety of methods have been reported for determining the serum level of paraquat or diquat, for example, thin-layer chromatography, 1) spectrochemical analysis, [2][3][4][5][6][7][8] HPLC, [9][10][11][12][13][14][15][16][17][18][19][20][21] LC/MS, 11) GC 22) and GC/MS. 23) In 1998, the Japanese Ministry of Health, Labor and Welfare distributed HPLC-photodiode array systems to 73 emergency centers throughout the country in order to facilitate the diagnosis of acute poisoning by drugs and poisons.…”
mentioning
confidence: 99%